Presentation of the study "DCH Observatory - Talent Management in Spain 2016" - Cruz, Rita Moreira da (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
DCH - Asociación Internacional de Directivos de Capital Humano (DCH) is an association of people with responsibilities in HR, whose main objective is to develop all areas within the Human Capital direction in organizations and associations facilitating the exchange of experiences, initiatives or news between its members in their different countries. (www.orgdch.org) This study is promoted by the DCH, with research partner EAE Business School, with the collaboration of the Human Age Institute. The objective of this study was to know the opinion of the members of the DCH on the most relevant projects and trends in Talent Management in all HR areas, to obtain a real image of People Management in Spain. The main idea is to create an observatory of People Management and, in this sense, this is the first study of what is intended to be an annual study, in order to verify the evolution every year. As for the methodology, this research has a non-experimental and transversal character. We designate non-experimental data, given that a certain number of variables are observed through an electronic questionnaire (Survey Monkey), to different observers without manipulation of these variables. And, we defined it as a transverse research character because it refers to a single moment (data collection took place between October and November 2016) to a particular group (people with responsibilities in the HR direction of Spanish companies). All the members of the DCH were invited to participate in the questionnaire, receiving a total of 124 responses, which allowed to carry out an analysis and later to obtain conclusions with statistical validity. Team Researcher Structure: EAE Business School Director of Campus Madrid: Raúl Bravo Principal Investigator: Pilar LLácer Researchers: Miguel Alcorta, Rita Moreira da Cruz, Rocío Rodríguez Barsallo, José Ignacio Slon Roblero DCH DCH President: Juan Carlos Pérez Espinosa Organization, HR and Institutional Relations Director in State Foundation for Training in Employment: Antonia Fernández Pineda HR Director Coca Cola: Marta Muñoz Willis Towers Watson: Laura González Lorenzo HR Director Orange: Pablo Carrillo Rodríguez HR Director Hewlett Packard Enterprise: Pilar Olondo. HR Vice President NH Hotels: Fernando Córdova Moreno HR Director Real Estate Credit Union: Ángel Aguilar The focus of this study was to analyze the 4 dimensions of people management cycle in companies: Attraction (How do we attract the best candidates for open positions?), Linking (How can we compromise our high potential so that they remain motivated?), Development How can we change behavior to maximize commitment, performance and improve performance?) And Disengagement (What can we do to make our former employees continue to be ambassadors of our company?). The results obtained in the Attraction dimension show a special interest in contracting Junior profiles, as well as in the use of incorporation Talent programs. In this line, the results show the importance of using Employer Branding strategies in order to make the company more attractive to current and future employees. Interim Management and Diversity Management Policies show, however, less penetration in most organizations. Regarding the Linking dimension, it is verified that the On-boarding / Immersion programs and the Commitment Management Policies and / or Strategies are already common practice in organizations. On the other hand, the Management of “Employees Experience", which aims to improve their performance and commitment, is not, however, a frequently used practice in Spanish companies. In relation to the Development dimension, the use of High Potential programs is highlighted, in particular for Middle Management positions and the use of Professional Career plans linked to the Performance Evaluation. On the other hand, there is a growing incorporation of Coaching and Mentoring Programs as new tools for the Training processes and a regression of the use of Elearning training. Finally, regarding to the dimension of Disengagement, it is evident that most people leave the organizations due to the lack of growing opportunities. Regarding the existence of Outplacement Programs, most of the companies surveyed do not use the service in question nor do they maintain further contact with the workers who are disengaged from the company.